Sejarah Bid’ah: Ashhab Al-Hadith Dan Dominasi Wacana Islam Autentik Pada Tiga Abad Pertama Hijriyah - Aceng Abdul Kodir (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2016)
The relationship between majorities and minorities in Islamic discourse is a result of the seizure of an authentic Islam. The discourse of authentic Islam in the history of Islamic society, rooted in the concept of heresy. This concept appeared due to the absence of religious authorities in a chaotic social dynamic. In the social political history of Islamic society, the ahlul hadith are the people who are responsible in introducing the concept of heresy as the opponent of the concept of sunna. This was motivated by the spirit of religiousity and the complexity of political nuance. As a result, the early Islamic historical discourse in the medieval was dominated by the opposition between heresy (bid’ah) narration and sunna. Through this opposition mainstreaming, the ahlul hadith stands as the narrators of the authentic Islam. In the contrary, religious narration outside the ahlul hadith is recognized as ahl al-ahwa’ wa al-bida’. This pejorative recognition, at the same time declared the victory of the ahlul hadith in propagating the authentic Islam and marked the emergence of opposition movement. This paper focuses on questions regarding the origin of heresy narration, the sunna and the discourse of authentic Islam. Methodically, some focuses will be analyzed by investigating the term of ahl al-ahwa’ wa al-bida’ used by the early ahlul hadith as mentioned in ‘ulum al-hadith’s books.